A Case Study of Learners’ Engagement in Mobile Learning Applications - Liu, Chenxi; Correia, Ana-Paula (Online Learning, 2021)
Although mobile learning applications play a crucial role in today’s education and can support learning, the low retention rate is a prevalent challenge in mobile learning. Existing studies have found that interpersonal interaction, high expectations, and supportive environment (from an educational perspective) as well as compatibility, interactivity, and usability (from a marketing perspective) can impact learners’ engagement in learning activities and customers’ engagement in mobile applications. However, comprehensive studies investigating learners’ engagement in mobile learning applications from educational and marketing perspectives are rare. To fill the research gap, we analyzed learners’ reviews on five top-ranked lifelong learning applications (Udemy, LinkedIn Learning, Coursera, edX, and Skillshare). Inductive coding was used to identify critical factors impacting learners’ engagement in mobile learning applications, such as usability, availability of learning experiences, features to facilitate learning, interpersonal interaction, and incentives for completion. We further explored specific engagement strategies displayed in the analyzed applications through an analytical evaluation. Besides, this study expands Hew’s model of learners’ engagement and suggests new conceptual relationships between critical factors impacting learners’ engagement, self-determination theory, and learners’ engagement.